2019
DOI: 10.1002/ijc.32391
|View full text |Cite
|
Sign up to set email alerts
|

Second primary cancers in non‐Hodgkin lymphoma: Family history and survival

Abstract: Second primary cancers (SPCs) account for an increasing proportion of all cancer diagnoses and family history of cancer may be a risk factor for SPCs. Using the Swedish Family‐Cancer Database on non‐Hodgkin lymphoma (NHL), we assessed the influence of family history on risk of SPCs and of SPCs on survival. NHL patients were identified from the years 1958 to 2015 and generalized Poisson models were used to calculate relative risks (RRs) for SPCs and familial SPCs. Among 14,393 NHL patients, a total of 1,866 (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Parameters tested were those published as risk factors for SPC, [1][2][3][4][5][6][7][8][9][10] age, sex, cancer types, metastatic disease at diagnosis as well as the application of immunotherapy and CC for the FPC. A backward selection procedure was used to determine the final model by removing non-significant variables (P > 0.05) one at a time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Parameters tested were those published as risk factors for SPC, [1][2][3][4][5][6][7][8][9][10] age, sex, cancer types, metastatic disease at diagnosis as well as the application of immunotherapy and CC for the FPC. A backward selection procedure was used to determine the final model by removing non-significant variables (P > 0.05) one at a time.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio associated with the risk of SPC as compared with the general population are reported to range from 1.2 up to 30 depending on the FPC and its treatment. [1][2][3][4][5][6][7][8][9][10] We recently reported that the administration of ICIs, mostly PD-1/PD-L1 or CTLA4 antibodies for the FPC, was associated with a reduced risk of Time to 2nd cancer (months) A B Figure 1. Time to second primary tumor according to the treatment given for the first primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations